Judas : a biography - Gubar, Susan, 1944- (New York : W.W. Norton, 2009)
An account of the story of the New Testament's arch-villain and his history over the past 2000 years in which Gubar links Christian anti-Semitism with Christianity's attempt to grapple with transcendent evil.
Introduction -- Part I: Mysterious origins -- Judas, fact or fiction? -- Alone of all his sex : Genesis in the Gospels -- Part II: Evolving incarnations -- Damned miscegenation : a fiendish adolescence from antiquity on -- Arresting kisses : coming of age, especially during the Renaissance -- In a modern glass darkly : the issue of sacrifice -- Twentieth-century deaths and resurrections : what would Judas do? -- Jesus, according to Judas's bad news : he who is praised.
Includes bibliographical references (p. [405]-429) and index.
Keywords: Judas Iscariot